The Lithuanian Language Seminar at the University of Königsberg: 1718–1723 - Aleknavičienė, Ona (Senoji Lietuvos literatūra, 2018)
The aim of the article is to analyse the initial stage of the activities of the Lithuanian Language Seminar at the University of Königsberg (Lith. Karaliaučius), which lasted from 1718 to 1723. Based on the letters of the first head of the seminar Heinrich Lysius (Lith. Henrikas Lyzijus, 1670–1731) to Friedrich Wilhelm I of Prussia (1688–1740) and to Professor August Hermann Francke (1663–1727) of the University of Halle, on the king’s rescripts regarding the improvement of the teaching system in Lithuania Minor (Prussian Lithuania, Lith. Prūsijos Lietuva), and on other archival documents and secondary sources, the article provides a description of the functioning of the seminar headed by Lysius, of the reasons behind the interruption of its activities, and of the circumstances leading to its reopening. Although the idea of the establishment of the Lithuanian Language Seminar at Königsberg University emerged in the summer of 1718, it can be seen from Lysius’s letter of 27 October 1718 to the king that the teaching process was not launched immediately: late in October, discussions revolved only about the future seminar and the matters of its founding. Organisational preparatory work and coordination of the conditions of the forthcoming activities took about half a year. It was only after 4 January 1719, that is, only in the summer term of 1719, when the issues of the stipends (one-third of all assigned stipends were foreseen for the seminar), the convictorium, and the alumni residence were resolved. Lysius’s letter of 31 July 1722 to Friedrich Wilhelm I shows that the seminar he headed functioned not just for one year as Martin Ludwig Rhesa (Lith. Martynas Liudvikas Rėza, 1776–1840, head of the seminar from 1810 to 1840) wrote in the history of the seminar Geschichte und Verfaßung des litthauischen Seminariums auf der Universitaet zu Königsberg (1811), but at least for two years and was entering its third year. Thus the teaching activities that started in the summer term of 1719 continued until the middle or the end of the summer term of 1721, that is, it completed four terms and started the fifth one. The seminar accepted young people sent from Lithuanian provinces. At the seminar, the students studied independently, but they were supervised by their tutor and examined by the consistory of Semba. When the skills of the Lithuanian language received positive grades, they were included among the candidates to work in Lithuania Minor, and at least three of them were dispatched to work as teachers in Klaipėda, Būdviečiai (Ragainė province), and Enciūnai (Įsrutis province) when vacancies occurred. The interruption in the activities of the seminar was not caused by a shortage of students of Lithuanian descent or the difficulties encountered by the Germans in learning Lithuanian, as Rhesa claimed in his history of the seminar Geschichte und Verfaßung des litthauischen Seminariums auf der Universitaet zu Königsberg and was supported by his followers, but by the king’s organisational decisions regarding the redistribution of ecclesiastical positions. The activities of the seminar were interrupted when after the death of the senior court preacher Bernhard von Sanden Jnr (on 22 January 1721; Lith. Bernhardas fon Zandenas jaunesnysis, 1666–1721) his place was filled not by Heinrich Lysius but by Evangelical Lutheran Johann Jakob Quandt (Lith. Jonas Jokūbas Kvantas, 1686–1772; introduced to the Castle Church on 9 March 1721). From the Castle Church, where he worked as the third preacher, Lysius was transferred to the position of a pastor at Löbenicht (Lith. Lyvenikė) church (introduced on 18 May 1721); also, his authority to supervise the churches and schools of Lithuania Minor was suspended and the duties of the supervision of churches and schools were passed on to Quandt on 22 September 1721. Archival documents (Lysius’s letter of 31 July 1722, W. H. von Mansberg’s letter of 25 June 1722, and others) show that in summer 1722, the revival of the seminar became a matter of great concern on the initiative of the king and his milieu. The re-opened seminar might have started work in the winter term of 1723–1724, after Quandt and W. H. von Mansberg had prepared its statute (approved on 20 May 1723). According to the statute, the seminar was to be headed by the senior court preacher and thus this position went to Quandt. The order foreseen by the statute differed slightly from the one introduced by Lysius: in addition to lectures, the seminar participants were to gather for two hours every day, and to study theology for one hour in the morning and the Lithuanian language for one hour (and not two, as it was under Lysius) in the afternoon. The establishment of the Lithuanian Language Seminar at the University of Königsberg was one of the essential steps while implementig compulsory primary education in Lithuanian in Lithuania Minor.